Analisis Tuturan dalam Ritual Su’i Uwi Upacara Adat Reba Masyarakat Doka Kecamatan Jerebu’u Kabupaten Ngada (Kajian Semiotika Ferdinand de Saussure) - Kristina Natalia Kodhe; Marselus Robot; Margareta (Lembaga Yasin AlSys, 2026)
Although the Su’i Uwi ritual is an important part of the Reba traditional ceremony of the Doka community in Jerebu’u Subdistrict, Ngada Regency and encompasses cultural, social, spiritual, and historical values, the meanings of its ritual utterances have not been extensively examined from a semiotic perspective. This study aims to describe the meanings of the utterances in the Su’i Uwi ritual based on Ferdinand de Saussure’s semiotic theory. This study employed a qualitative descriptive method, with data collected through interviews, observation, and documentation. The research informants included a tribal leader, the head of a traditional house, and elders who understood the performance of the Su’i Uwi ritual. The findings show that the Su’i Uwi ritual in the Reba traditional ceremony consists of three main stages: Ka Ngagha Olo, Bura Su’a, and Su’i. The semiotic analysis indicates that the relationship between the signifier and the signified in the ritual utterances constructs ritual, spiritual, social, moral, cosmological, historical, and practical meanings. These meanings represent respect for ancestors, expressions of gratitude to God, cultural identity, the value of togetherness, the relationship between humans and nature, and customary norms governing the lives of the Doka community. This study concludes that the utterances in the Su’i Uwi ritual function not only as a medium of symbolic communication but also as a means of transmitting cultural values and strengthening community identity. The findings of this study contribute to the development of semiotic studies of oral traditions and support efforts to preserve the local culture and wisdom of the Ngada community.